Pengaruh Desain Pelatihan, Lingkungan Kerja Non-Fisik, dan Self-Efficacy Terhadap Transfer Pelatihan Pitstop Akreditasi di Rumah Sakit Nur Hidayah Yogyakarta - Yati Suhartini; Widya Rahayuningsih; Hari Purnama (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
This study aims to determine the effect of training design, non-physical work environment and self-efficacy on the transfer of the 2022 accredited Pitstop training at Nur Hidayah Hospital, Yogyakarta. The study used a quantitative research approach with 80 respondents as research subjects. The respondents in question were Nur Hidayah Hospital Yogyakarta employees who had participated in the 2022 accreditation Pitstop training. Primary data was collected by distributing questionnaires through the Google form application. While data processing uses the Statistical Program for Social Science (SPSS) application version 20.0. Furthermore, data analysis was carried out with Multiple Linear Regression. The results of the analysis show that the training design partially has a positive and significant effect on training transfer with a regression coefficient of 0.353 and a significance value of 0.000. The non-physical work environment has a positive and significant effect on training transfer with a regression coefficient of 0.241 and a significance value of 0.000. Self-efficacy has a positive and significant effect on transfer of training with a regression coefficient of 0.268 and a significance value of 0.000. Furthermore, training design, non-physical work environment and self-efficacy simultaneously have a significant effect on training transfer with a significance value of 0.000. Therefore, all hypotheses in this study are accepted.